Bisphenol A and Male Reproductive System - Amraje, Fatma F. Mohamed; Köylü, Ayşe; Dizakar, Saadet Özen Akarca; Türkoğlu, İsmail; Omeroglu, Suna (My University, 2018)
Bisphenol A (BPA) is an alkylphenol endocrine disruptor chemical (EDC). It is abuilding block for polycarbonate (PC) plastics and epoxy resins and it is usedin food packaging, canned foods, baby bottles, baby food jars and medicaldevices. Recently, researchers have shown an increased interest in BPA and itseffect on reproduction, neurodevelopment and metabolism. Theexperimental data are rather controversial, and there is no general consensusabout BPA’s effects. In this review, potential impacts of the BPA on malereproductive system in prenatal and postnatal period are summarized.
Keywords: Kadın Hastalıkları ve Doğum; Endokrinoloji ve Metabolizma; Biyokimya ve Moleküler Biyoloji